1986
DOI: 10.1002/j.1556-6676.1986.tb01323.x
|View full text |Cite
|
Sign up to set email alerts
|

Needed: Competent, Confident, and Committed Career Counselors

Abstract: Gelso, C., Prince, J., Cornfeld, J., Payne, A., Royalty, G., & Wiley, M. (1985). Quality of counselors intake evaluations for clients with problems that are primarily vocational versus personal. Journal of Counseling Psychology, 32, 339–347. Pinkney, J., & Jacobs, D. (1985). New counselor's and personal interest in the tasks of career counseling. Journal of Counseling Psychology, 32, 454–457.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1987
1987
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Additional support for the contention that participant characteristics influenced the marked preference for the social/depression hypothesis over the academic/anxiety hypothesis comes from research indicating that counselors prefer to work with personal problems, as compared with vocational problems (Dorn, 1986; Gelso et al, 1985; Pinkney & Jacobs, 1985); it is possible that counselor preference for the academic issue presented in the current study was more similar to the vocational category. Recent work on “vocational overshadowing” (Spengler, Blustein, & Strohmer, 1990) has described a similar effect.…”
Section: Discussionmentioning
confidence: 67%
“…Additional support for the contention that participant characteristics influenced the marked preference for the social/depression hypothesis over the academic/anxiety hypothesis comes from research indicating that counselors prefer to work with personal problems, as compared with vocational problems (Dorn, 1986; Gelso et al, 1985; Pinkney & Jacobs, 1985); it is possible that counselor preference for the academic issue presented in the current study was more similar to the vocational category. Recent work on “vocational overshadowing” (Spengler, Blustein, & Strohmer, 1990) has described a similar effect.…”
Section: Discussionmentioning
confidence: 67%
“…The clients' reactions to the counseling interview were also seldom noted or discussed. Many new counselors also express little interest in working with clients who have career problems because they view career counseling as a stepchild of personal and social counseling and much prefer the role of psychological counselor, ironically because of its emphasis on affective/dynamic issues (Dorn, 1986;Pinkey & Jacobs, 1985).…”
Section: Caroline Manuele-adkins Is a Professor In The Department Of mentioning
confidence: 99%
“…Given the historic import and unique relationship of vocational counseling to counseling psychology, it is ironic that Tyler (1959) observed a tendency for psychologists working in counseling centers to view educational–vocational counseling as routine and less important than personal counseling. Since Brayfield (1961) and Samler (1964) expressed concerns that vocational emphases in counseling psychology were being devalued, additional studies have shown that vocational counseling has been termed dull by practitioners and that vocational clients were treated in a routine or secondary fashion by counselors who were not as disposed toward conducting careful intake evaluations with vocational clients as they were with clients with personal problems (Dorn, 1986; Graff & Maclean, 1970; Graff, Raque, & Danish, 1974; Melnick, 1975).…”
mentioning
confidence: 99%